"Don't need [therapy]! Not necessary, that's what we're for!": Does content from fibromyalgia Facebook peer support groups emulate psychological flexibility principles? - Lyndsay Crump; Diane LaChapelle (Elsevier, 2023)
Objective: Many persons with fibromyalgia (FM) use online peer support groups (OPSGs) to address unmet emotional or psychological needs. Some OPSG members have suggested that participation in an OPSG is a viable substitute for professional psychological services, however, no published research exploring this claim was identified. Methods: Discussion content collected from three Facebook FM OPSGs was thematically analyzed to explore whether the content posted in FM OPSGs emulated content consistent with the psychological flexibility model underlying Acceptance and Commitment Therapy (ACT) - an evidence-based psychotherapy for chronic pain conditions. Results: The content posted in OPSGs did not emulate and often contradicted the core psychological flexibility processes or skills emphasized in ACT programs. Conclusion: Participation in an FM OPSG should be approached cautiously. Content from the FM OPSGs should not be considered a substitute for professionally delivered ACT, although participation may provide emotional support to help individuals move towards readiness for active psychotherapy. Innovation: This research represents a novel application of the psychological flexibility model underlying ACT to assess the potential therapeutic value of a peer support community. Additionally, it is the first to clarify that content in FM OPSGs is not aligned with psychological flexibility processes.